DR. HAJI MUSA ALI RECEIVES INTERNATIONAL RECOGNITION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 3 August 2015 – The Director of the Centre for Innovation and Productivity in Public Administration (PIPPA) Dr. Haji Musa Ali recently has been appointed as a Visiting Fellow at the University of Palermo, Italy – the only fellow to be appointed from among those from the Asian countries.